Performance of Porous-Venturi Microbubble Generator for Aeration Process - Lathifa Putri Afisna; Wibawa Endra Juwana; Indarto Indarto; Deendarlianto Deendarlianto; Fellando Martino Nugroho (University of Muhammadiyah Malang, 2017)
Qualified and preserved water is declining due to metal, waste, and hazardous chemicals contamination. Demand on fresh water raises and leads to the efforts on processing waste water with effective and efficient technology. Microbubble generator technology developed lately to result dissolved oxygen for raising microorganisms to decompose waste in waste water. This research used porous-ventury microbubble generator with 30° inlet angle and 20° outlet angle, placed in the center of 280 cm x 60 cm x 40 cm aquarium for experiment. This research aimed to find out bubble distribution and microbubble generator (MBG) performance. Measurement on bubble distribution conducted using Phantom Control Camera. Obtained data analyzed using MATLAB R2016a, while MBG performance measured using pressure transducer. Analysis conducted on variations of gas debit (0,1 lpm; 0,4 lpm., and 1 lpm) and water debit (30- 80 lpm) effects toward performance parameters, such as hydraulic power (Lw) and bubble generating efficiency (ηB). Results show that the greatest microbubbles’ diameter is 150- 500 μm, hydraulic power (Lw) increases with the inclining water debit (QL), effect of gas debit variation exert low effect towards Lw, and declining number of bubble generating efficiency (ηB) parameter with the inclining number of the water debit (QL).